2021
DOI: 10.1037/xhp0000953
|View full text |Cite
|
Sign up to set email alerts
|

Target–background segregation in a spatial interference paradigm reveals shared and specific attentional mechanisms triggered by gaze and arrows.

Abstract: Recent research has found that eye gaze and arrows yield opposite congruency effects in a spatial interference paradigm, arrows eliciting faster responses when their direction is congruent with their position (standard congruency effect), and gaze producing faster reaction times for incongruent conditions (reversed congruency effect). In addition, we observed by serendipity in a previous study that the standard effect with arrows was reduced when the target appeared within a complex background, presumably beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 45 publications
(85 reference statements)
4
11
0
Order By: Relevance
“…Whereas, surprisingly, with social stimuli (full faces and cropped eyes), slower RTs and more errors were observed for congruent versus incongruent trials. This effect observed on social stimuli, referred to by the authors as reversed congruency effect (Cañadas & Lupiáñez, 2012), has been repeatedly replicated since then (Aranda-Martín et al, 2022; Edwards et al, 2020; Ishikawa et al, 2021; Jones, 2015; Marotta et al, 2018, 2019; Narganes-Pineda et al, 2022; Román-Caballero et al, 2021a, 2021b; Torres-Marín et al, 2017). Recently, the same pattern of standard and reversed congruency effects, for arrows and gaze, respectively, has been replicated through a within-participant counterbalanced blocked design (Marotta et al, 2018).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Whereas, surprisingly, with social stimuli (full faces and cropped eyes), slower RTs and more errors were observed for congruent versus incongruent trials. This effect observed on social stimuli, referred to by the authors as reversed congruency effect (Cañadas & Lupiáñez, 2012), has been repeatedly replicated since then (Aranda-Martín et al, 2022; Edwards et al, 2020; Ishikawa et al, 2021; Jones, 2015; Marotta et al, 2018, 2019; Narganes-Pineda et al, 2022; Román-Caballero et al, 2021a, 2021b; Torres-Marín et al, 2017). Recently, the same pattern of standard and reversed congruency effects, for arrows and gaze, respectively, has been replicated through a within-participant counterbalanced blocked design (Marotta et al, 2018).…”
mentioning
confidence: 73%
“…For example, variables known to reduce spatial congruency effects with arrows could be manipulated to investigate whether they simultaneously increase reversed congruency effects for gaze trials. In this regard, presenting directional targets surrounded by irrelevant context has been found to reduce the spatial congruency effect produced by arrows trials, while leading to a corresponding increase in the reversed congruency effect observed in gaze trials (Román-Caballero et al, 2021a, 2021b).…”
Section: Discussionmentioning
confidence: 97%
“…However, this might be for a different reason. As shown by Román-Caballero et al, (2021a, 2021b, this could be due to the fact that the Simon effect, which is present for both arrows and gaze, is eliminated when the targets (either arrows or eyes) are surrounded by a complex background, i.e., the whole face, from which they need to be segregated. The cropped eye stimuli are the same from the whole face, and therefore we consider that the same result would be observed with whole faces (i.e., no implicit RCE) as similar effects are observed for cropped eyes and whole faces when the effect of the background is taken into account (see Román-Caballero et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Simon effect and spatial Stroop effects). According to his hypothesis, the location activation peaks and decays immediately after target onset, so location conflicts would resolve when a temporal gap between location code and response is formed (Hommel, 1993;Juncos-Rabadán et al, 2008;Proctor et al, 2011;Román-Caballero et al, 2021a, 2021b. Román-Caballero et al (2021a) claimed that complex target backgrounds consumed more time for target extraction than simple ones (e.g.…”
Section: Eye Gaze Is Not Specialmentioning
confidence: 99%